(untitled) (Theatrum historiae, 2012)
The hospital foundation established by Franz Anton Sporck stands out of the Count’s other activities, but we still know very little about its history. In the study the author sets out to capture the complicated circumstances of its formation from the initial intention at the end of the 17th century, via the detailed preparation of the institution’s statutes in 1711 to its successful launch in 1744. The study pays special attention to the foundation’s financial backup provided not only by the founder, but also by his heirs, as well as the establishment of a hospital ward with partial information about its operation in the first years.